2021
DOI: 10.1002/ajpa.24437
|View full text |Cite
|
Sign up to set email alerts
|

An osteometric and 3D analysis of the atlanto‐occipital joint: An initial screening method to exclude crania and atlases in commingled remains

Abstract: Objectives: The anatomical features of the atlanto-occipital joint can be potentially useful in re-associating or excluding crania to atlases in commingled remains. This study investigated whether linear measurements and the 3-dimensional (3D) surface of occipital condyles and articular facets of atlases can represent valid insights for this purpose. Methods:The variations among eight corresponding linear distances were analyzed in a sample of 150 individuals through six supervised machine learning techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The affiliated laboratory LAFAS is equipped with the stereophotogrammetric device Vectra M3 (Canfield Scientific, Inc.), whose ability to accurately reproduce the virtual model of the object has been validated [25]. Although the reproduction of meshes from bare bones is still to be extensively explored, this device has been recently employed to acquire models for the re-association of articulating bones [26]. Nonetheless, such device was suitable for the acquisition of the planar structure of the innominate bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The affiliated laboratory LAFAS is equipped with the stereophotogrammetric device Vectra M3 (Canfield Scientific, Inc.), whose ability to accurately reproduce the virtual model of the object has been validated [25]. Although the reproduction of meshes from bare bones is still to be extensively explored, this device has been recently employed to acquire models for the re-association of articulating bones [26]. Nonetheless, such device was suitable for the acquisition of the planar structure of the innominate bone.…”
Section: Discussionmentioning
confidence: 99%
“…Stereophotogrammetry, particularly the device used in this study (VECTRA-3D® M3: Canfield Scientific, Inc., Fairfield, NJ), is among the gold standard techniques for 3D surfaces acquisition [40,41]; moreover, its ability to automatically re-build the geometry of the surface is beneficial time-wise. The affiliated laboratory is equipped with the above-mentioned stereophotogrammetry machine, which has been successfully used in recent publications to acquire bone surfaces [26]. It thus represents a valuable tool for the reproduction of bone models which is worth exploring within the field of virtual anthropology.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a reference sample and a validation sample were examined to assess the potential of this novel method in reassociating commingled sacra and os coxae. Despite the illustrated benefits of sorting mixed joint articulations, the greater part of the published literature concerns pair‐matching or elemental associations [1, 9, 18–22, 25, 27, 46–59]. Of the few studies examining the utility of sorting commingled joints, the majority focus on joint congruence at the atlanto‐occipital joint [17, 26, 29, 56, 57] or at the large joints of the body, such as the hip or knee [12, 18–20, 23, 29, 30, 60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dudar and Castillo [26] found that the shape of the occipital condyles and the atlas were only congruent within individuals 23%–25% of the time, and Puerto et al [56] found that reassociations at the atlanto‐occipital joint were only moderately reliable, with a correct match ranging from 60% to 90% of the time. Cappella et al [57] most recently generated RMS values between atlanto‐occipital articular surfaces and selected the highest true articulation value as their threshold. While 100% of true pairs were correctly classified, only 32% of true negative pairs were identified [57].…”
Section: Discussionmentioning
confidence: 99%
“…None of the rTEM values in this study fall within the 1.5% intraobserver error or 2% inter‐observer error thresholds outlined by Langley et al [15] (based on Perini et al [16]) for osteometric measurements. However, Cappella et al [17] uses a 7.5% threshold for both intra‐ and interobserver error for atlanto‐occipital measurements. In a study of virtual femoral measurements, Ismail et al [18] indicates that measurements with coefficients of reliability <0.9 and rTEMs >5% should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%